Impulse and Momentum Linear Teaching Materials with Al-Quran Verses to Practice Problem Solving Skills of Students: Practicality and Effectiveness - Yayan Azhary; Mastuang Mastuang; Dewi Dewantara (Universitas Nurul Huda, 2022)
This study aims to describe the practicality and effectiveness of impulse and linear momentum teaching materials containing verses of the Koran to train students' problem-solving skills. This research is research and development (R&D) using the ADDIE model and tested on 12 students of class X MIPA 1 MAN 2 Banjarmasin. Data collection was obtained through a questionnaire instrument for student responses, and a test of students' cognitive learning outcomes and analyzed descriptively quantitatively. The results showed that: (1) teaching materials obtained a fairly practical category with a score of 2.48, (2) teaching materials obtained in the less effective category the N-gain value is 0.13 with a low category. It was concluded that the teaching materials were quite practical but not effective for practicing problem solving skills